Strongly Pseudo Nearly Semei-2-Absorbing Submodules (II) - Al Dury, Mohmad Essa Dahash; Mohammadali, Haibat K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Let  be a module over a commutative ring  with identity. Before studying the concept of the Strongly Pseudo Nearly Semi-2-Absorbing submodule, we need to mention the ideal  and the basics that you need to study the  concept of the Strongly Pseudo Nearly Semi-2-Absorbing submodule. Also, we introduce several characteristics of the Strongly Pseudo Nearly Semi-2-Absorbing submodule in classes of multiplication modules and other types of modules. We also had no luck because the ideal  is not a Strongly Pseudo Nearly Semi-2-Absorbing ideal. Also, it is noted that  is the Strongly Pseudo Nearly Semi-2-Absorbing ideal under several conditions, which is this faithful module, projective module, Z-regular module and content module and non-singular module and content module. Also we introduce the characterization of the concept of the Strongly Pseudo Nearly Semi-2-Absorbing ideals by a special kind of submodule